"This will drive them wild…wild": Comptroller James Saxon's transformation of American banking, 1961-1966. Issue 4 (2nd October 2019) - Storrs, Thomas B.
ABSTRACT: James J. Saxon sought to transform American banking as Comptroller of the Currency, the regulator of national banks, from 1961 to 1966. As a regulatory entrepreneur, he attempted to unleash what he perceived as overly regulated national banks in order to stimulate the American economy. Saxon impacted many small towns by chartering new banks and breaking up 'Rotary Club cartels.' He loosened many regulations, induced numerous banks to switch to national charters, and sparred with fellow regulators and Congress, but ultimately failed to implement much of his agenda. The half century that followed saw his vision realized as the American financial sector occupied a historically disproportionate fraction of the economy. Saxon marks an inflection point between aggressive New Deal financial regulation and the deregulatory movement leading up to the Great Recession. Saxon serves as an example of the dangers in zeal outstripping tact in efforts to effect organizational change. He also provides an anomalous example of a bureaucrat breaking from the stereotype of colorless evenhandedness. As memories of the Great Recession fade, Saxon serves as an example of the risks of a deregulatory process and the importance of a delivery mechanism for ideas for today's bankers, regulators, and public officials.